2011
DOI: 10.1002/rra.1481
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Salmon Response to the Placement of Engineered Log Jams (Eljs) in the Elwha River, Washington State, Usa

Abstract: Engineered log jams (ELJs) are increasingly being used in large rivers to create fish habitat and as an alternative to riprap for bank stabilization. However, there have been few studies that have systematically examined how juvenile salmonids utilized these structures relative to other available habitat. We examined Chinook salmon (Oncorhynchus tshawytscha), coho salmon (O. kisutch) and trout (O. mykiss and O. clarki) response to the placement of engineered log jams (ELJs) in the Elwha River, Washington State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…As early as the 1930s, Tarzwell (1937) called for more rigorous monitoring and evaluation to determine physical and biological effectiveness. Since then, many studies have reported improved habitat and fish production, particularly for salmonid fishes (e.g., Binns 1999;Hunt 1976;Pess et al 2012;Roni and Quinn 2001a;Shetter et al 1949; for a review, see Roni et al 2008), whereas others have reported no detectable changes (e.g., Chapman 1996;Rosi-Marshall et al 2006;Stewart et al 2009;Thompson 2006).…”
Section: Biological Response To Wood Placementmentioning
confidence: 99%
“…As early as the 1930s, Tarzwell (1937) called for more rigorous monitoring and evaluation to determine physical and biological effectiveness. Since then, many studies have reported improved habitat and fish production, particularly for salmonid fishes (e.g., Binns 1999;Hunt 1976;Pess et al 2012;Roni and Quinn 2001a;Shetter et al 1949; for a review, see Roni et al 2008), whereas others have reported no detectable changes (e.g., Chapman 1996;Rosi-Marshall et al 2006;Stewart et al 2009;Thompson 2006).…”
Section: Biological Response To Wood Placementmentioning
confidence: 99%
“…Freshwater habitat is important to Pacific salmonid species as some spend one or more years rearing in river systems as juveniles (Meehan and Bjornn, 1991). Structural cover elements in stream channels, such as in-stream large wood (LW), also serve an important role in sheltering juveniles from predation and in reducing water velocities (Bjornn and Reiser, 1991;Hafs et al, 2014) such that LW quantities are often positively associated with juvenile salmonid abundance (Cederholm et al, 1997;Benke and Wallace, 2003;Pess et al, 2012). Metabolic efficiency and growth rate depends on stream temperature and availability of food sources (Becker and Genoway, 1979;Murphy and Meehan, 1991), in addition to dissolved oxygen and turbidity levels (Bjornn and Reiser, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Pess et al. () hypothesized that the density of juvenile salmonids in habitat units with engineered logjams decreased as the number of logjams in their study reach increased from 8 to 19 during 2000–2003. This suggests either that juvenile abundance was at carrying capacity before the placement of additional logjams or that fish had not yet fully responded to the placement of logjams that were added during the study period.…”
Section: Does the Size Or Amount Of River Restoration Influence Fish mentioning
confidence: 92%